Species-Specific Class I Gene Expansions Formed the Telomeric 1 Mb of the Mouse Major Histocompatibility Complex - Takada, Toyoyuki; Kumánovics, Attila; Amadou, Claire; Yoshino, Masayasu; Jones, Elsy P.; Athanasiou, Maria; Evans, Glen A.; Lindahl, Kirsten Fischer (Genome Research, 2003)
We have determined the complete sequence of 951,695 bp from the class I region of H2, the mouse major histocompatibility complex (Mhc) from strain 129/Sv (haplotype bc). The sequence contains 26 genes. The sequence spans from the last 50 kb of the H2-T region, including 2 class I genes and 3 class I pesudogenes, and includes the H2-M region up toGabbr1. A 500-kb stretch of the H2-M region contains 9 class I genes and 4 pseudogenes, which fall into two subfamilies,M1 and M10, distinct from other mouse class I genes. This M1/M10 class I gene-cluster is separated from the centromeric H2-T and the telomeric H2-M4, -5 and-6 class I genes by “nonclass I genes”. Comparison with the corresponding 853-kb region of the human Mhc, which includes the HLA-A region, shows a mosaic of conserved regions of orthologous nonclass I genes separated by regions of species-specific expansion of paralogous Mhc class I genes. The analysis of this mosaic structure illuminates the dynamic evolution of the Mhc class I region among mammals and provides evidence for the framework hypothesis.[Supplemental material is available online at www.genome.org. The sequence data from this study have been submitted to GenBank under accession nos. AC005413, AC005665,AF532111–AF532117. A preliminary draft sequence was earlier submitted as AC002615 and replaced this year by NT002615.]
10.1101/gr.975303